Inhibitory activity of flavonoids fraction from Astragalus membranaceus Fisch. ex Bunge stems and leaves on Bacillus cereus and its separation and purification - Cui, Liyan; Ma, Zhennan; Li, Wenhui; Ma, Haihui; Guo, Shang; Wang, Defu; Niu, Yanbing (Frontiers in Pharmacology, 2023)
Introduction: Astragalus membranaceus Fisch. ex Bunge is a traditional botanical drug with antibacterial, antioxidant, antiviral and other biological activities. In the process of industrialization of A. membranaceus, most of the aboveground stems and leaves are discarded without resource utilization except for a small amount of low-value applications such as composting. This study explored the antibacterial activity of the A. membranaceus stem and leaf extracts to evaluate its potential as a feed antibiotic substitute. Materials and methods: The antibacterial activity of flavonoid fraction, saponin fraction and polysaccharide fraction in A. membranaceus stems and leaves was evaluated by disk diffusion method. The inhibitory activity of flavonoid fraction from A. membranaceus stems and leaves on B. cereus was explored from the aspects of growth curve, cell wall, cell membrane, biofilm, bacterial protein and virulence factors. On this basis, the flavonoid fraction in A. membranaceus stems and leaves were isolated and purified by column chromatography to determine the main antibacterial components. Results: The flavonoid fraction in A. membranaceus stems and leaves had significant inhibitory activity against B. cereus, and the Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were 1.5625 and 6.25 mg/mL, respectively. A. membranaceus stem and leaf flavonoid fraction can induced the death of B. cereus in many ways, including inhibiting growth, destroying cell wall and cell membrane integrity, inhibiting biofilm formation, inhibiting bacterial protein synthesis, and down-regulating virulence factor expression. In addition, it was clear that the main flavonoid with antibacterial activity in A. membranaceus stems and leaves was isoliquiritigenin. Molecular docking showed that isoliquiritigenin could form hydrogen bonding force with FtsZ. Conclusion: A. membranaceus stem and leaf flavonoid fraction had significant inhibitory activity against B. cereus, and the main chemical composition was isoliquiritigenin.